Hunters, Warriors, Monsters - Ford, Shannon (John Wiley & Sons, 2013)
No doubt the years hunting monsters and saving the universe have had their toll on the Winchesters, but their toughest and most gruesome battles are contained in this book. Think Lucifer was diabolically clever? Think again.